Disulfide-containing polyamidoamines with remarkable flame retardant activity for cotton fabrics. (October 2018) - Manfredi, Amedea; Carosio, Federico; Ferruti, Paolo; Alongi, Jenny; Ranucci, Elisabetta
Abstract: Bioinspired polyamidoamines containing disulfide-groups in the main chain (SS-PAAs), prepared by Michael polyaddition of 2, 2-bis(acrylamido)acetic acid with l -cystine (B-CYSS) and of N, N′-bis(acryloyl- l - cystine) with either glycine or 2-methylpiperazine (BACYSS-GLY and BACYSS-MP), were investigated as intumescent surface-confined flame retardants for cotton textiles. The main purpose was to ascertain if the presence of disulfide functions in the repeat units imparted superior flame retardant properties compared with sulfur-deprived polyamidoamines whose efficacy were previously demonstrated. In horizontal flame spread tests, at 18% add-on both BACYSS-GLY and BACYSS-MP inhibited ignition; at 12% add-on BACYSS-GLY extinguished flame, whereas BACYSS-MP burnt completely leaving substantial carbonaceous residues. In vertical flame spread tests, both BACYSS-GLY and BACYSS-MP burnt completely leaving substantial residues up to at least 18% add-on. At 12% add-on B-CYSS inhibited ignition in both horizontal- and vertical flame spread tests. In the latter test, only limited afterglow was observed. Scanning electron microscopy (SEM), thermogravimetric and cone calorimetric analyses were consistent with these results. In particular, thermogravimetric analyses showed at 750 °C high residues in nitrogen (28–54%) and only moderately lower residues in air (19–48%). In cone calorimetry tests, all tested SS-PAAs increased time to ignition, decreased peak of heat release rate and effective heat of combustion of cotton. All samples remarkably reduced CO and CO2 yields. SEM micrographs of combustion residues of all SS-PAAs treated cotton fabrics presented diffused intumescent bubbles. Graphical abstract: Highlights: Bioinspired polyamidoamines- bearing disulfide groups were studies as surface-confined flame retardants for cotton textiles. Disulfide-containing polyamidoamines exhibited higher flame retardant activity for cotton compared with sulfur-deprived ones. At 12% add-on the polyamidoamine from 2, 2-bis(acrylamido)acetic acid andl -cystine did not ignite in vertical flame spread tests.